MENINGKATKAN KUALITAS PELAYANAN RUMAH SAKIT JIWA MELALUI ANALISIS KINERJA PERAWAT DENGAN METODE BALANCE SCORECARD - Imas Masriah; Ongkong Sion (Inovasi, 2021)
This study aims to analyze the performance of nurses and service quality at the Anmarsu Hospice Care Mental Hospital. The research method used is a descriptive qualitative approach, by collecting primary data sources through interviews with the Managing Director of RSJ Anmarsu Hospice Care, the Chairperson of the Anmarsu Hospice Care Hospital, the Finance Department, and two secondary nurses obtained from reviewing employee quality improvement documents. The analysis used is the content analysis technique using the Balanced Scorecard measuring instrument. The results of this study consisted of three parts, namely the first part with an approach to overall measurement obtained 23 points x 2 = 46 points, the second part with a specific type of measurement approach to the organization obtained 140 points, and the third part with a reporting approach and data analysis obtained 48 points x 2 = 96 points. Based on the results of the overall score calculation, a total score of 282 points is obtained, which means that the Anamrsu Hospice Care Mental Hospital has a very good approach in measuring organizational performance.